Is Group Choice a Part of Economics? - Allin, Bushrod W. (Quarterly Journal of Economics, 1953)
Introduction, 362. — I. Ellis and the economic calculus of individual preference, 362. — II. Knight and the science of the price mechanism, 367. — III. Survey of economic education by McKee and Moulton, 373. — IV. Report on undergraduate teaching of economics, 374. — V. Summary, 377.